To determine the correct function that describes the relationship in the table, let's analyze the values provided.
The table shows the following pairs of \( (x, y) \):
- For \( x = 0, y = -5 \)
- For \( x = 1, y = -9 \)
- For \( x = 2, y = -13 \)
- For \( x = 3, y = -17 \)
By examining the changes in \( y \) as \( x \) increases, we can identify the pattern.
The changes in \( y \):
- From \( -5 \) to \( -9 \) is a decrease of 4 (\(-9 - (-5) = -4\))
- From \( -9 \) to \( -13 \) is a decrease of 4 (\(-13 - (-9) = -4\))
- From \( -13 \) to \( -17 \) is a decrease of 4 (\(-17 - (-13) = -4\))
This indicates that the function is linear with a slope of -4.
To find the equation of the line, we can use the slope-intercept form \( y = mx + b \), where \( m \) is the slope and \( b \) is the y-intercept. Given the slope is -4, we can start with:
\[ y = -4x + b \]
Now, we need to find \( b \). We can use any of the points; for example, let's use \( (0, -5) \):
\[ -5 = -4(0) + b \] \[ b = -5 \]
Thus, the equation becomes:
\[ y = -4x - 5 \]
In function notation, we write this as:
\[ f(x) = -4x - 5 \]
Therefore, the correct response is:
f(x)=−4x−5